Anesthetic efficacy and safety of ropivacaine 0.75% versus bupivacaine 0.5% for spinal anesthesia in patients undergoing lower limb orthopedic surgery - Pratiti J Gohil; Pankti Panchal; Gauri M. Panjabi; Jinal J. Gohil; Ushma H. Thakar; Raghav R. Rathi (Asian Journal of Medical Sciences, 2023)
Background: Ropivacaine, a new amino-amide local anesthetic agent, is similar in chemical structure to bupivacaine. The low solubility of ropivacaine leads to greater sensory-motor differentiation by blocking sensory nerve fiber more readily than motor nervefibers. Early recovery of motor function is associated with decreased incidence of venous thromboembolism and early mobilization.